Near space radiation dosimetry in Australian outback using a balloon borne energy compensated PIN diode detector. (November 2016) - Mukherjee, Bhaskar; Wu, Xiaofeng; Maczka, Tomasz; Kwan, Trevor; Huang, Yijun; Mares, Vladimir
Abstract: This paper reports the near space ballooning experiment carried out at Australian outback town West Wyalong (33°51′S, 147°24′E) on 19 July 2015. Several dedicated electronic detectors including digital temperature and acceleration (vibration) sensors and an energy compensated PIN-diode gamma ray dosimeter were installed in a thermally insulated Styrofoam payload box. A 9 V Lithium-Polymer battery powered all the devices. The payload box was attached to a helium-filled latex weather balloon and set afloat. The balloon reached a peak burst altitude of 30 km and then soft-landed aided by a self-deploying parachute 66.2 km away form the launch site. The payload box was retrieved and data collected from the electronic sensors analysed. The integrated cosmic ray induced photon ambient dose equivalent recorded by the PIN diode detector was evaluated to be 0.36 ± 0.05 μSv. Furthermore, a high-altitude extended version of commercially available aviation dosimetry package EPCARD.Net (E uropeanP rogram package for theC alculation ofA viationR outeD oses) was used to calculate the ambient dose equivalents during the balloon flight. The radiation environment originated from the secondary cosmic ray shower is composed of neutrons, protons, electrons, muons, pions and photons. The photon ambient dose equivalent estimated by the EPCARD.Net code found to be 0.47 ± 0.09 μSv. The important aspects of balloon based near-space radiation dosimetry are highlighted in this paper. Highlights: Near space ballooning experiment in Australian outback. A PIN diode based gamma dosimeter was sent to an altitude of 30 km. Ambient photon dose equivalent was evaluated as a function of altitude. Results agreed well with the simulated data delivered by EPCARD.Net Code. The atmospheric temperature and payload jerks were also assessed.